Sistem Pembayaran UKT Online Bagi Mahasiswa Politeknik Negeri Sriwijaya Berbasis Android - Dinda Amaniska; Lindawati Lindawati; Martinus Mujur Ros (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2019)
The design of online UKT payment applications is based on the writer's desire to help Sriwijaya Polytechnic students in facilitating several daily support activities with an easier and more practical process, especially in this case related to online UKT payments. Thus the author intends to design an application online UKT payment system which in this study the author uses several programming languages such as Java, PHP, and My SQL then supported by the use of the waterfall method through the stages of design, modeling, construction, and submission of the system to users which ends with the stages of device usage in the final results The author uses this waterfall method hoping to minimize errors because as we know this method uses the one by one phase development process. The completion of this application is expected to be useful in the community, especially student students. i Sriwijaya State Polytechnic in making online UKT payments that can be used on their respective smartphones